PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN FACIAL WASH GLAD2GLOW PADA PLATFORM SHOPEE - Redittia, Muhammad; Rachmansyah, Arief (Komunitas Manajemen Kompetitif, 2026)
ABSTRACT This study aims to analyze the influence of product quality, price, and promotion on the purchase decision of Glad2Glow Facial Wash products on the Shopee e-commerce platform. This research employs a quantitative approach using a survey method. Data were collected through online questionnaires distributed to 99 respondents who are Shopee users and have previously purchased Glad2Glow Facial Wash products. The data analysis technique used Structural Equation Modeling–Partial Least Square (SEM-PLS). The research model explains 73.8% of the variance in purchase decisions (R² = 0.738). These findings suggest that promotional strategies are the primary factor driving consumer purchase decisions on e-commerce platforms. Keywords: product quality, price, promotion, purchase decision, e-commerce